2017
DOI: 10.4467/16890027ap.17.011.7486
|View full text |Cite
|
Sign up to set email alerts
|

Rat spleen in the course of Babesia microti invasion: histological and submicroscopic studies

Abstract: The course of babesiosis in humans is characterized by various intensity levels − from a subclinical level to the severe one − associated with multiple organ failure, which leads to death. The aim of this study was to evaluate the effect of 21-day and 6-month invasion of B. microti on Wistar rats spleen. Histological changes in the rats' spleen were characterized by swelling of splenic tissue, especially the tissue adjacent to the capsule. In the structure of the white pulp in some rats, high concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Many damaged cells were also observed in the area of blood vessels, and the cytoplasm of these cells contained a large amount of glycogen and residual bodies. The presence of platelets adhering to the surface of damaged cells, near the vacuole, was also observed [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many damaged cells were also observed in the area of blood vessels, and the cytoplasm of these cells contained a large amount of glycogen and residual bodies. The presence of platelets adhering to the surface of damaged cells, near the vacuole, was also observed [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The course of experimental infection by the B. microti (Franca) Reichenow ATCC 30221 strain in laboratory rats has been studied in our department for many years. We found that Wistar rats succumbed to infection by this strain of B. microti, which caused quite a few changes in the organs of these animals [8,9].…”
Section: Introductionmentioning
confidence: 90%